TEACHING FOREIGN LANGUAGES IN AN INTERCULTURAL WORLD (Conferencea, 2024)
This article explores the challenges and strategies in teaching foreign languages in an increasingly intercultural world. It examines the importance of intercultural competence, the role of language teachers, and the methodologies that can foster both linguistic and cultural understanding in students. The study outlines effective pedagogical approaches and suggests that integrating intercultural elements into language instruction can enhance students' ability to navigate a diverse global society. The findings highlight the need for teachers to be not only language experts but also facilitators of cultural exchange.